PENGGUNAAN HURUF KANJI OLEH PEMBELAJAR BAHASA JEPANG DI PROGRAM STUDI SASTRA JEPANG UNIVERSITAS HASANUDDIN (Universitas Negeri Jakarta, 2015)
Research related to Kanji usage by Hasanuddin University Japanese Department student is a type of feedback in order to understand how students react to a certain kanji teaching method. This is a qualitative research, and the subject of research is 60 Japanese Department students from 1st to 3rd year students. Research result showed that subjects cannot write well-proportioned kanji, incorrect stroke or stroke order. Incorrect writing tend to cause wrong interpretation or even make the kanji have no meaning at all. 1st and 3rd year students tend to use more hiragana and less kanji in Writing Class than 2nd year students.